PHET and PBL: Do They Work Well Together in Improving Mathematical Critical Thinking and Problem Solving Ability? - Kusaeri, Kusaeri; Lailiyah, Siti; Indayati, Tatik (FKIP Universitas Lampung, 2022)
Does Problem-Based Learning Integrated into PHET Improve Mathematical Critical Thinking and Problem Solving Ability? Objectives: This research aims to examine the effectiveness of the use of PBL combined with PHET rather than PBL about mathematical critical thinking and problem-solving ability. Methods: This research employed an experimental approach involved a sample of 63 students of grade VIII’s favorite MTs in Sidoarjo Regency, East Java, divided into 2 classes (PBL class combined with PHET and regular PBL class). The data were analyzed with descriptive statistics combined with Mann-Whitney’s statistical test. Findings: This research finds out that there is no difference in the influence of the intervention on the application of PBL combined with PHET with the usual PBL group in developing students' mathematical problem-solving ability, and there are differences in the influence of interventions on the implementation of PHET integrated PBL and the application of ordinary PBL in developing students' mathematical critical thinking ability. Conclusion: Based on findings, the importance of providing adequate computer facilities for students when they want to implement website-based learning media such as PHET. Keywords: PHET, PBL, problem solving, critical thinking, and mathematics.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202215